Historical christianity in Brazil - Santos, Marcos Danilo Lima dos; Nascimento, Oslei do; Ribeiro, Sérgio Adriano; Magalhães, Leandro Henrique (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Teologia, 2022)
Christianity, since its foundation, with the expected messiah, presents historical facts of struggles and persecutions. The disciples of Jesus Christ, believed in their words, and they understood that He was the messiah. The announcement of the Word of God, was a challenge to call new adherents to the Messianic doctrine. Many of the great preachers found barriers to the word of the Lord, be spread according to your true teachings. With the abuses of the papacy, religious leaders felt motivated to protest, thus emerging new denominations of Churches. In Brazilian lands, the religious predominance of Portugal, in the 16th century, was a milestone of struggles between protesters who sought freedom religious, and the Portuguese reign that sought to dispel the invasions, mainly with the help of the Jesuit priests. in the 19th century, freedom religious began to have great strength, both on the part of religious who remained steadfast in this conquest, and liberals holding great positions politicians. Thus, in the 20th century, several Pentecostal movements emerged that changed the forms of traditional worship, bringing a revival within the Church. With religious pluralism, the idea of a dialogue between religions emerged, in order to contribute to peace and brotherhood in the world. The purpose of the work is to bring the main forms of religiosities that Christianity provided during the centuries of its existence, highlighting the religious struggles in the Brazilian colonial period, with the Portuguese domination, even its freedom of worship, its changes and allegiances. To formulate this work, several references from books related to the topic were used, with scathing investigations. The work, it provided real discoveries of the trajectory of Christianity in Brazilian lands, in addition to arousing curiosity for further research on the topic.